An Editor bows out - Tribute to former Editor, Prof. Anthony Ebeigbe as he retires (Nigerian Journal of Physiological Sciences, 2020)
This tribute was written to appreciate the longest-serving Editor-in-Chief in the history of this journal as he retires from active teaching and research. His contributions to the Physiological Society of Nigeria is outstanding and his relationship with colleagues highly commendable.